Peran Keluarga Terhadap Perilaku Mahasiswa yang Mengkonsumsi Minuman Beralkohol di Kabupaten Jember - Nina Ainur Rahma; Husni Abdul Gani; Mury Ririyanti (Pustaka Kesehatan, 2020)
Adolescents in the age range of 17-21 years are generally students, who are expected to have good cognitive skills and be able to solve problems effectively. Teenagers who are unable to solve problems sometimes do something that is harmful to themselves such as consuming alcoholic beverages. The role of the family such as parenting and family conditions is one of the causes of adolescents consuming alcoholic beverages. This study aims to determine the role of families in the behavior of students who consume alcoholic beverages in Jember Regency. The theory used by researchers is Social Learning from Bandura. This research is a descriptive study with a qualitative approach. Determination of research informants using snowball techniques. Data collection uses in-depth interviews, documentation and passive participatory observation. Based on the results of the study it was found that the all-free parenting style, lack of trust given by parents to involve children in making decisions and ineffective time spent by parents for families so that children behave deviant. Keywords: Family, teenagers, alcoholic drinks, social learning